Factors Affecting Compliance WITH Financial Accounting Standards of Entity Without Public Accountability (SAK ETAP) In MSMEs In Bada Village - SUBHAN, Ega Saiful; SUDARMIATIN, Sudarmiatin; HERMAWAN, Agus (PT Keberlanjutan Strategis Indonesia, 2021)
Other causes of neglect of recording/financial reports from MSMEs are the lack of understanding and expertise in recording, the education level of business managers who still have not achieved the expertise/application technology in making SAK ATAP financial report documents. This study aims to determine whether the level of education, information technology and age of business affect SAK ETAP compliance on MSMEs in Bada Village. The type of research used in this research is quantitative with a descriptive approach. The population in this study was 66 and the sample obtained was 40 MSME actors. The data collection technique used in this research is a questionnaire and analysis tool, namely multiple regression using the SPSS 21.0 application. The results showed that both simultaneously indicated that the level of information technology education and business age had a positive and significant effect on SAK ETAP compliance. Partially the level of education has a significant effect on SAK ETAP compliance where the value of sig. Partially, information technology has a significant effect on SAK ETAP compliance where the value of sig . Partially, business age has a significant effect on SAK ETAP compliance where the sig value